The Pelican Brief - Grisham, John (London Arrow Books Ltd., 1993)
wo Supreme Court Justices are dead. Their murders remain unsolved. Darby Shaw, a brilliant and beautiful New Orleans legal student, draws up a speculative legal brief which links the deaths and uncovers an astonishing presidential conspiracy. When her boyfriend is atomised in a car bomb, it becomes clear that somebody is intent on silencing Darby for good. Somebody who will stop at nothing to preserve the secrets of the Pelican Brief...
Keywords: Women Law Students -- Journalists